PENGARUH KERJA SAMA TIM DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT STELLA MOBILI KOTA TANGERANG SELATAN - Juan Habel Hantingan; Dede Andi (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of teamwork and work discipline on employee performance at PT Stella Mobili, South Tangerang city. This type of research uses quantitative methods. The sampling technique used a slovin sample and obtained 93 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of this study are teamwork has a significant effect on employee performance by 67.8% and hypothesis testing obtained tcount> ttable, namely (13.843> 1.661). Work discipline has a significant effect on employee performance with a coefficient of determination of 74.9% and hypothesis testing obtained tcount> ttable, namely (16,500> 1,661). Teamwork and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 3.321 + 0.339X1 + 0.596X2, the coefficient of determination is 78.7% while the remaining 21.3% is influenced by other factors. Hypothesis testing obtained Fcount> Ftabel or (165.900> 3.098).